ChemInform Abstract: Cyano‐Schmittel Cyclization Through Base‐Induced Propargyl‐Allenyl Isomerization: Highly Modular Synthesis of Pyridine‐Fused Aromatic Derivatives. Issue 17 (April 2016) - You, Xu; Xie, Xin; Chen, Haoyi; Li, Yuxue; Liu, Yuanhong
Abstract: Pyridine‐fused polycyclic skeletons can be conveniently constructed in a one‐pot manner through cascade Sonogashira coupling of terminal cyano‐ynes with organic halides, followed by base‐promoted propargyl‐allenyl isomerization/cyclization.